(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Minimally invasive spine surgery (MISS) has emerged as an alternative to conventional open spine surgery for lumbar degenerative disorders, aiming to reduce tissue damage and improve recovery while maintaining comparable outcomes. Objective: To compare perioperative and clinical outcomes between minimally invasive and open spine surgical techniques. Material and Methods: This prospective case series was conducted at Pranav Hospital, Dindugal, from January 2025 to January 2026. Ten patients with lumbar degenerative conditions were included and divided into two groups: MISS (n=5) and open surgery (n=5). Parameters evaluated included operative time, intraoperative blood loss, hospital stay, pain using Visual Analog Scale (VAS), functional outcome using Oswestry Disability Index (ODI), and complications. Patients were followed for 6 months. Results: The MISS group showed significantly reduced blood loss (180 ± 40 mL vs 420 ± 60 mL) and shorter hospital stay (3.2 ± 0.8 days vs 6.4 ± 1.1 days) compared to the open group. Operative time was slightly longer in the MISS group. Both groups demonstrated significant improvement in VAS and ODI scores, with comparable outcomes at 6 months. Complications were observed only in the open surgery group. Conclusion: MISS provides better perioperative outcomes with similar functional recovery compared to open surgery. It is a safe and effective alternative for selected patients, although larger studies are required for confirmation.